Integrasi Kecerdasan Digital dan Keterampilan Adaptif Abad ke-21 - Arini Nuora Darina; Tiara Nurul Annisa'; Misbahul Arifin; Juwita; Toyyibatul Mukminatus Sukriyah (Educational Research Center, 2025)
This research focuses on innovative public relations (PR) strategies in addressing the reconstruction of the quality of Islamic education in the era of disruption, emphasizing the importance of integrating digital intelligence and strengthening 21st-century adaptive skills. The background of this research is based on the urgent need for Islamic educational institutions, particularly madrasas, to respond to global challenges through collaborative, visionary, and value-based communication approaches. This study uses a qualitative approach with case study methods on Islamic education units in the Probolinggo region. Data collection techniques include in-depth interviews, direct observation, and documentation analysis. The results show that PR strategies that combine the use of digital technology, strengthening Islamic character, and 21st-century skills such as critical thinking, collaboration, and effective communication, can enhance stakeholder participation, strengthen the institution's image, and and building public trust. The implications of this research emphasize that the reconstruction of the quality of Islamic education requires the active role of PR as a strategic transformation agent, while also serving as a guardian of spiritual values amid disruptive waves of change.